Cultivation systems on common root rot and take-all of wheat - Diehl, J. A.; Kochhann, R. A.; Tinline, R. D. (Pesquisa Agropecuaria Brasileira, 2014)
The effect of cultivation systems on the intensity of common root rot and take-all in wheat (Triticum aestivum L.) fields was determined in Rio Grande do Sul in 1980 and 1981. Common root rot occurred in all surveyed fields. Its intensity was high in fields cropped annually to wheat and in those maintained out of wheat for one and two years regardless of the other crops grown. Disease was much less intense in fields that had been left fallow for three or four years or that were planted to wheat for the first time. Cochliobolus sativus (Ito & Kurib.) Drechsl. ex Dastur was the dominant pathogen isolated from lesioned wheat roots. Take-all occurred in about 30% of the fields annually cropped to wheat or that either had been left fallow or planted to a non-host crop such as flax, lupine, oats, or rapeseed for one year. It was not found in wheat following two or more years of oats, fallow, or a combination of fallow and a non-host crop. The average disease ratings in 1980 and 1981 were 60% and 71%, respectively.